Application of physiologically-based pharmacokinetic/pharmacodynamic models to evaluate the interaction between nifedipine and apatinib - Liu, Hongrui; Yu, Yiqun; Liu, Lu; Wang, Chunyan; Guo, Nan; Wang, Xiaojuan; Xiang, Xiaoqiang; Han, Bing (Frontiers in Pharmacology, 2022)
Aim: The aim of the present study was to evaluate the pharmacokinetic as well as the pharmacodynamic (PD) drug-drug interaction (DDI) between nifedipine and apatinib. Meanwhile, the rational combination regimen in patients with hepatic impairment was also assessed. Methods: We firstly developed a physiologically-based pharmacokinetic (PBPK) model for nifedipine. The pharmacokinetic DDI between nifedipine and apatinib was evaluated. Then the verified PBPK models were linked to a PD model to investigate whether the exposure changes of nifedipine could cause severe changes in blood pressure. Furthermore, the changes in blood pressure caused by combination of apatinib were also assessed in patients with hepatic impairment via the PBPK/PD models. Results: The predicted area under plasma concentration-time profile (AUC), maximum concentration (Cmax), area under effect-time profile (AUE), and maximum reduction in systolic blood pressure (Rmax), were all within 0.5-2.0-fold of the observed data. PBPK/PD models for nifedipine were successfully established. The predicted AUC and Cmax increases of nifedipine in the presence of apatinib was 1.73 and 1.41-fold, respectively. However, the predicted AUE and Rmax changes of nifedipine in the presence to the absence of apatinib in cancer patients and hepatic impairments were all within 1.25-fold, indicating that the exposure changes of nifedipine caused by combination of apatinib had little effect on the systolic blood pressure both in cancer patients and hepatic impairments. Conclusion: Apatinib was unlikely to cause severe pharmacodynamic DDI via inhibition of CYP 3A4. Thus, nifedipine could be used in combination with apatinib without dose adjustment in clinic.